2011
DOI: 10.3171/2010.12.spine10233
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and cost-effectiveness analysis of external beam and stereotactic body radiation therapy in the treatment of spine metastases: a matched-pair analysis

Abstract: Object The objective of this study was to compare the palliative efficacy and cost effectiveness of external beam radiation therapy (EBRT) to stereotactic body radiation therapy (SBRT) as primary treatment for bone metastatic disease of the spinal column. Methods Forty-four patients were matched based on age, primary tumor site, year of treatment, and location of metastasis. Outcomes of interest were pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 9 publications
1
51
0
6
Order By: Relevance
“…Refinement of the combination of a number of these strategies has improved clinical outcome and the quality of life of many patients, although as many as 50% of patients will require further intervention for recurrent pain. 7,14 External-beam radiation therapy remains the mainstay of adjuvant therapy for spinal metastases and offers significant short-term and, in some instances, long-term palliation. Although 30 Gy in 10 fractions is the most common fractionation schedule, multiple fractionation schemes have been reported.…”
mentioning
confidence: 99%
“…Refinement of the combination of a number of these strategies has improved clinical outcome and the quality of life of many patients, although as many as 50% of patients will require further intervention for recurrent pain. 7,14 External-beam radiation therapy remains the mainstay of adjuvant therapy for spinal metastases and offers significant short-term and, in some instances, long-term palliation. Although 30 Gy in 10 fractions is the most common fractionation schedule, multiple fractionation schemes have been reported.…”
mentioning
confidence: 99%
“…Cohorts were followed up during their remaining lifetimes; the Markov cycle length was 1 month. The Markov model is shown in Figure 1 representing transition probabilities between health states based on medical literatureebased treatment outcome and survival rates (Table 1) (1,(17)(18)(19)(20)(21). For our model calibration, Markov cohort probability analysis was performed for the expected survival rates for both SBRT and EBRT cohorts.…”
Section: Methods and Materials Decision Modelmentioning
confidence: 99%
“…Sahgal et al [1] proposed that SRS is approximately 3-4 times as expensive as CRT. Haley et al [16 ]also compared SRS with CRT, and concluded that SRS is more costly than CRT. In addition, when we consider that SRS is a newly emerging technique and that there may be a need for improved equipment and software, the higher costs in the SRS group were predictable.…”
Section: Discussionmentioning
confidence: 99%